Integrated energy planning to meet 2050 European targets: A Southern Italian region case study. (May 2022) - Battaglia, V.; De Luca, G.; Fabozzi, S.; Lund, H.; Vanoli, L.
Abstract: The Campania Region has one of the highest renewable energy potentials in Italy. Despite this high potential, the lack of an integrated energy strategy has allowed for deregulated exploitation of the resources of the territory, e.g. surplus of wind energy occurs in Campania due to the large wind farms, geothermal energy is mainly used for thermal baths but its enthalpy could meet domestic heating demand, etc. A lack of an "integrated planning", does not to make the best use of resources and to contribute to greenhouse gas (GHG) emission reduction. The aim of this work is to develop a possible scenario for achieving sustainable energy condition towards decarbonization in the Campania Region. The 2030 'transition scenario' is characterized by a reduction in GHG emissions. In the 'Campania 2050' scenario, the region's energy system is mostly reliant upon biomethane and other local renewable resources. The new methodology, based on the classification of climatic zones, was designed to meet the hourly energy and production demands of both current and future energy plants in the territory. Different software tools were used to find a new integrated renewable energy system for Campania. The software EnergyPLAN was used to design the entire system and assess the integration of the different sectors (electric, thermal, and transport), and TRNSYS 17 and DesignBuilder were used to achieve the desired hourly energy production of individual plants. The results obtained show that the 2030 'transition' scenario is characterized by a reduction in the "1990 CO2 emissions" of approximately 45%. The 'Campania 2050' scenario achieves the decarbonization objective of reducing the GHG emissions by 80% with respect to the 1990 values by combining different energy efficiency strategies, relying upon renewable energy sources, and electrifying the transport sector. Highlights: An Integrated energy planning for Campania satisfying the European and Italian targets of reducing CO2 emissions by 2050 was developed. Data on each measure identified to make the Campania Region a zero-carbon territory was input into EnergyPLAN evaluating the effects on the energy balance. To obtain the hourly energy demand curves, a new methodology based on the classification of climatic zones was applied. The use of software tools allowing a dynamic analysis of the energy system becomes necessary to obtain roboust results. The flexibility of the energy system with a high integration RES was assessed considering the compromise coefficient, namely COMP.